Existência de uma solução positiva para um problema assintoticamente linear ou superlinear em domínio exterior - (:unkn) unknown (Universidade Federal do Amazonas, 2020)
In this work we study an asymptotically linear or superlinear problem in the external domain in order to show the existence of a weak and positive solution. To guarantee the existence of this solution, we use some variational techniques, compactness techniques, a topological argument and a barycenter function.
Keywords: Variedade de Nehari; Sequência de Palais - Smale; Limite assintoticamente linear; Baricentro; Abordagem variacional; CIÊNCIAS EXATAS E DA TERRA; Variedade de Nehari; Domínio Exterior; Sequência de Palais - Smale; Baricentro